Large Capital Flows : A Survey of the Causes, Consequences, and Policy Responses - Lopez Mejia, Alejandro (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews the causes, consequences, and policy responses to large capital flows in several emerging markets. It opens by studying recent patterns of capital flows, and then discusses the causes of capital flows. Emphasis is given to the reasons behind the capital inflow episode in the 1990s, the major reversals, and the volatility observed in these flows. The paper goes on to examine the consequences of capital inflows and the pros and cons of alternative policy responses. It concludes with policy lessons derived from country experiences.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet